Pengaruh Efisiensi dan Efektivitas Pendapatan Terhadap Hutang Kredit Pada CV.Nusantara Tour Tahun 2017-2021 - Naisah Saputri Nst; Nahar Marganda Saragih (Student Research Journal, 2023)
Credit for ordinary people is defined as debt, debt is goods or services that must be paid back to the lender with terms agreed upon by both parties.This study aims to determine the effect of Credit Debt (Debt to Asset Ratio) on Efficiency and Effectiveness of Income at CV. Nusantara Tour Company. In this research, the researcher uses quantitative associative. Data were collected by observation and documentation methods and then analyzed by financial ratios. In this study, the data sources used were primary and secondary data collection in the form of annual financial reports from CV. Nusantara Tour.This study aims to determine how the influence of Credit Debt (Debt to Asset Ratio) on the efficiency and effectiveness of the company's income.Based on the results of the study, it shows that Credit Debt (Debt to Asset Ratio) proves that partially has a negative and significant effect on Income Efficiency, proving that partially Debt to Asset Ratio has a negative and significant effect on Income Effectiveness, Credit Debt (Debt to Asset Ratio) proves that simultaneously has a significant and significant effect on the efficiency and effectiveness of CV.Nusantara Tour's company income.